UTILIZATION OF NATURAL RESOURCES OF RUMAH GALUH IN THE PRODUCTION OF LIQUID ORGANIC FERTILIZER (POC) FROM BAMBOO SHOOTS - Delyana R Pulungan; Tifany Zia Aznur; Dina Arfianti Saragih; Ritna Wahyuni; Rina Maharany; Ade Junesa; Nurhida Yani Lubis; Bifrans Andre Batubara; Dimas Napitupulu; Khairul Imam; Sayyid Murtadhah Nst1 (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
This community service activity was carried out in Rumah Galuh Village, Sei Bingai sub-district, Langkat Regency. The Liquid Organic Fertilizer (POC) demonstration was carried out for 1 day and was attended by local residents with the aim of making people aware that liquid organic fertilizer is an alternative to chemical fertilizer. Apart from being environmentally friendly, POC can also be made by yourself by utilizing the natural wealth in their village. The problem with the Galuh house community is chemical fertilizers whose prices are unaffordable because chemical fertilizers, which can be categorized as expensive to buy, make people lazy to fertilize their plants. Bamboo shoots are one of the natural resources that can be used as POC. Bamboo shoots are a material that can be used as organic fertilizer because they contain organic materials and other ingredients that can increase plant growth. Bamboo shoots contain the hormone gibberalin, phosphorus 59mg, calcium 13mg, iron 0.5mg, potassium 20.12mg. The content of the gibberalin hormone and these nutrients will be useful in stimulating the growth of oil palm seedlings and possibly reducing the dose of NPK fertilizer used when fertilizing oil palm seedlings. PKM ITSI MEDAN students conducted socialization to the Rumah Galuh community about procedures for making POC. The benefits of POC itself can support the development of environmentally friendly agriculture, and can produce materials that are free from chemical content and become an environmentally friendly alternative to chemical fertilizers.